ANALISIS FIQIH MUAMALAH PENGARUH PAYLATER TERHADAP PERILAKU KONSUMTIF MASYARAKAT PENGGUNA PAYLATER DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Hasanah, Siti Rohmatun; Thantawi, Tubagus Rifqy; Melinasari, Susi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This research is motivated by increasingly rapid technological developments that use the internet so that transactions and buying and selling today can be done online, one of which is e-commerce. Then e-commerce provides a new feature, namely paylater, namely buying products or goods that can be paid for next month or according to the proposed tempo, therefore it is in great demand by the public, especially the middle and lower classes so that it can make people fall into consumptive behavior. Based on the general description above, the purpose of this study is to determine the effect of paylater on the consumptive behavior of the middle and lower classes in the study of fiqh muamalah. The research method used is the quantitative method. The data obtained from Google Forms were distributed to a number of respondents with the object under study and the sample results obtained from Google Forms were distributed to as many as 300 respondents. The variables of this research are Paylater (X1) , Riba (X2), Ownership (X3), and Consumptive Behavior (Y). To test the level of reliability using Croancbach's Alpha. With a significant level of 5%. The research used SPSS Version 25 tool. The results of this study state that: paylater variables (X1), usury (X2) and ownership (X3) have a positive and significant effect on the consumptive behavior of middle and lower class people with a significance value of 0.000 <0.05 (5%). As well as in the study of muamalah fiqh, the use of paylaters is found in the legalization of usury and seller ownership which is analyzed in X1 and X2 that is that the community agrees on the existence of interest and agreements when buying and trusts in purchasing a product so that it can be concluded that the use of paylaters according to the public's view is appropriate in the study of muamalah fiqh.